Dysphagia in older adults with mild cognitive impairment and dementia through fluoroscopic study with barium swallow in a memory clinic - Martinez-Peña, Georgina; Mimenza-Alvarado, Alberto Jose; Aguilar-Navarro, Sara Gloria (Frontiers in Neurology, 2025)
IntroductionDysphagia and cognitive impairment are prevalent in older individuals. This study aimed to understand the characteristics of dysphagia through fluoroscopy in older adults with mild cognitive impairment (MCI) and dementia.MethodsA cross-sectional study was conducted at a memory clinic in a tertiary hospital in Mexico City. A total of 158 patients were included, of whom 86 (54.4%) showed a risk of dysphagia, and 84 underwent barium swallow fluoroscopy.ResultsAn association was observed between MCI and alteration in the oral phase (OR 0.33, 95% CI 0.12, 0.92, p = 0.034). Compared to patients with dementia, patients with MCI showed greater alteration in protection against regurgitation (OR 3.19, 95% CI: 1.05 to 9.72, p = 0.042) and in the contraction of the laryngeal muscles (OR 3.54, 95% CI: 1.30 to 9.62, p = 0.013).DiscussionOur findings highlight the altered phases of swallowing in patients with dementia. Additionally, we found a high prevalence of dysphagia in older adults with MCI, underscoring the importance of early detection and intervention.